The Embrace of Justice and Peace: Concerning the Tension Between Retributive and Eschatological Justice - Roko Kerovec (Kairos (English Ed.))
The article dialectically examines two Christian notions of justice: retributive and eschatological. Retributive justice denotes its expression through retaliation for sin, and eschatological justice implies its realization of complete harmony of all relationships within the renewed creation. The latter is called eschatological because, in distinction from the former, its full expression is attained through the final renewal of all creation in Christ – the eschaton which does not cancel out space and time but promotes them in perfection into eternity. The argument of the article advocates the primacy of the eschatological notion of justice within the Christian perspective, while its retributive character is being downplayed and subordinated to the logic of the former. This is accomplished through the integration of the Old and New Testament eschatologies as well as the criticism of dualistic tendencies within Christianity which inspire the prevalence of the retributive notion of justice and are actually alien to the Bible. Closely tied to the question of the character of justice is the question of the awareness of hell within Christian thinking and preaching. While the argument of the article does not question the existence of hell as the eternal state/place of the damned, it removes it from the central place it often occupies in Christian thinking.